How to differentiate between ‘Leadership’ and ‘Management’ Function in Organization: A Review of Scholarly Thoughts - Ali, Akbar (International Journal of Economics, Business and Management Studies, 2013)
The purpose of writing this article is to clearly differentiate between the concept of management which performs the just maintenance job and of the leadership which is an innovative term perceived as more effective and needed. Current scholarly literature on the topic has thoroughly been investigated which strongly supported the hypothesis that a leader is better than a manager. Mintzberg (1973; 1975), Kotter (1990) and Covey (2003) emphasized the requirement to develop the leaders than the managers in the organizations. Even the managers already working and performing efficiently can also be developed and converted into leaders by organizing appropriate training and mentoring for them. The lucky organizations and leaders are those who have intrinsically embraced this paradigm shift from management to leadership and are religiously following the required course of action towards bright future.